Coping with the worst of both worlds: phenotypic adjustments for cold acclimatization benefit northward migration and arrival in the cold in an Arctic breeding songbird - Le Pogam, Audrey; O'Connor, Ryan S.; Love, Oliver P.; Petit, Magali; Régimbald, Lyette; Vézina, François (Zenodo, 2021)
Cold acclimatization (phenotypic adjustments to cope with cold conditions) is an imperative requirement for birds living at high latitudes during the cold depths of winter. Despite the significant remodelling of key phenotypic traits and energetic costs associated with elevating cold endurance, winter cold acclimatization can also provide further carryover benefits to subsequent stages in species wintering, migrating and breeding in cold environments (e.g., the Arctic). We tested this beneficial carryover hypothesis using outdoor captive Arctic-breeding snow buntings ( Plectrophenax nivalis ), a cold specialist known for its impressive wintering thermogenic capabilities. We compared changes in phenotypic traits supporting cold acclimatization – body composition (body, fat, lean mass, pectoral muscle thickness), oxygen carrying capacity (hematocrit), thermogenic capacity and endurance (M sum , time to M sum ), cold tolerance (T a at M sum ) and maintenance energy expenditure (BMR) – between the wintering, migratory and arrival/summer stages. Body mass (+31%), fat mass (+226%), and BMR (+13%) increased relative to the winter phenotype, likely to support the added costs of migration - that is the migratory upregulation hypothesis . In contrast, lean mass, pectoral muscle thickness, hematocrit and thermogenic capacity remained high and stable at winter level across stages in support of the thermal carryover hypothesis. The maintenance of these traits likely offers spare capacity for unpredictable cold environments expected during migration and breeding in the Arctic. Our results thus suggest that birds can extend the long-term advantages of winter phenotypic adjustments through additional benefits to thermogenic capacity during subsequent life history stages. These benefits likely make it possible for Arctic-breeding birds to maximize success across diverse life history stages in the face of extreme cold conditions.